1998
DOI: 10.1002/(sici)1096-9861(19980413)393:3<353::aid-cne7>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Golgi study of the rat cerebellar molecular layer interneurons using principal component analysis

Abstract: In this study, we applied for the first time a multivariate analysis to describe the anatomy of cerebellar molecular layer interneurons. Forty variables extending over a variety of morphological features (geometrical, topological, and metrical) were obtained from a three-dimensional reconstruction of 26 rat rapid Golgi-stained neurons. The subsequent principal component analysis showed that the first principal component was strongly correlated with variables related to the depth of each cell's soma in the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
107
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 55 publications
16
107
0
Order By: Relevance
“…In cell-attached patches from SC boutons, we recorded K + currents mediated by both K v 1 and K v 3 type channels. The same current complement has also been reported for the pinceau axon specializations of cerebellar basket cells (Southan and Robertson, 2000), a closely related interneuron type in the molecular layer (Sultan and Bower, 1998). Although currents mediated by both K v 1 and K v 3 channels contribute to AP repolarization in the boutons of some cell types (Hoppa et al, 2014; Ritzau-Jost et al, 2014), we found that the conductance carried by K v 3-mediated currents predominates when driven by an AP-like waveform from a physiological resting membrane potential likely explaining why AP repolarization is determined by this channel type rather than K v 1 (Rowan et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…In cell-attached patches from SC boutons, we recorded K + currents mediated by both K v 1 and K v 3 type channels. The same current complement has also been reported for the pinceau axon specializations of cerebellar basket cells (Southan and Robertson, 2000), a closely related interneuron type in the molecular layer (Sultan and Bower, 1998). Although currents mediated by both K v 1 and K v 3 channels contribute to AP repolarization in the boutons of some cell types (Hoppa et al, 2014; Ritzau-Jost et al, 2014), we found that the conductance carried by K v 3-mediated currents predominates when driven by an AP-like waveform from a physiological resting membrane potential likely explaining why AP repolarization is determined by this channel type rather than K v 1 (Rowan et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…Stellate cell dendrites extend for several hundred micrometers sagittally, perpendicular to PF orientation (Palay and Chan-Palay 1974; Sultan and Bower 1998). Consistent with this anatomy, many responding interneurons were found well outside the region of PF beam activation.…”
Section: Recruitment Of Interneuronsmentioning
confidence: 80%
“…This method was successfully used in research on neuron morphology (e.g. Yelnik et al, 1983;Harpering et al, 1985;Pearson et al, 1985;Sultan and Bower, 1998;Sultan et al, 2003). PCA has some advantage over cluster analysis and other multivariate methods, as for example discriminant analysis.…”
Section: Discussionmentioning
confidence: 99%